Position of State Institutions in Indonesian Constitution - Triadi, Irwan (Faculty of Law, Universitas Pekalongan, 2022)
This research is about the position between state institutions, in this case the People's Consultative Assembly, the People's Representative Council, the Regional Representative Council, the Constitutional Court and the President as an important part of Constitutional Law. The Indonesian Constitution in this case is the 1945 Constitution of the Republic of Indonesia (before amendments and after amendments) which is divided into a Preamble and Body and is based on and based on Pancasila which is the source of Indonesian legal order. The method used in this research is normative legal research, namely research by examining library materials or secondary data which includes research on legal principles and legal systematics, research on the synchronization of legislation from a vertical and horizontal angle, which is carried out as an effort to obtain data necessary in connection with the problem. Prior to the amendment to the 1945 Constitution of the Republic of Indonesia, the highest state power was in the hands of the People's Consultative Assembly, as the incarnation of the entire Indonesian people. The President must carry out State policy according to the broad lines established by the Assembly. After the amendment to the 1945 Constitution of the Republic of Indonesia, the People's Consultative Assembly maintained its existence and was positioned as a state institution, but its position was no longer as the highest institution but as a state institution that was on an equal footing with other existing state institutions, including the Regional Representative Council. as a new institution to optimize and confirm the understanding of popular sovereignty and the Constitutional Court which gives the authority to be the guardian of the constitution. This research aims to provide an explanation of the position of state institutions in this case the People's Consultative Assembly, the People's Representative Council, the Regional Representative Council, the Constitutional Court and the President in the 1945 Constitution of the Republic of Indonesia (before amendments and after amendments)